МІФОЛОГІЧНА КУЛЬТУРА ЕПОХИ РОМАНТИЗМУ - Бурковський, М. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Аналізуються романтичні концепції міфу, що сформувались в Німеччині в кінці XVIII – на початкуXIX ст. Міфологія розглядається крізь призму творчості провідних авторів-міфологів, представниківромантичних шкіл тогочасності.Бурковский М. В. Мифологическая культура эпохи романтизма. Анализируются романти-ческие концепции мифа, сложившиеся в Германии в конце XVIII – начале XIX вв. Мифологиярассматривается сквозь призму творчества ведущих авторов-мифологов, представителей роман-тических школ того времени.Ключевые слова: немецкий романтизм, культура, миф, мифология, символ.M.V.Burkovsky. Mythological culture of the romantic era. Romantic conceptions of myth, which hasdeveloped in Germany in the late XVIIIth – early XIXth centuries are analyzed. The mythology is viewed throughthe prism of the creativity of leading authors-mythologists, representatives of the romantic schools of the time.Thus, since the dawn of German Romanticism, an artistic, literary, and intellectual movement that originated inEurope toward the end of the XVIIIth century, artists and intellectuals in Germany have maintained an keepinghigh interest in the gods and myths of antiquity while calling for a “new mythology” suitable to the modern age.In this article the author examines the factors that gave rise to such distinct and profound mythologicalconcernment. In doing so, he examines the major German romantic movement centers of those years. One ofthese groups is “Jena Romanticism”, which was a first phase of Romanticism. Brothers A. W. and F. vonSchlegel, Novalis and L. Tieck and certainly F. W. J. von Schelling, the “philosophical maitre” of theassociation, were members of this group. Mythology, as they believed, – is nothing but inherently common to allnations, and specific myths – are not the result of deliberate and conscious effort of the individual, but the resultof unconsciously, spontaneously, involuntary activities of many people. Gradually mythological studies ofRomantics shift from philosophical to specific scientific study of mythology. This romantic writers (which workedin another center of German Romanticism, Heidelberg) has employed specific, primarily German nationalmythmaking. J. Grimm was the author of the fundamental two-volume study “German Mythology”, which untilnow is considered as a classical work of comparative mythology. Thus, author demonstrates, that the era ofRomanticism became as a kind of foundation stone in the historical development of myth philosophy, which isrightly considered as a “core” of cultural and intellectual life in Germany in the late XVIIIth – early XIXthcenturies. The fascination with philosophical (speculative) aspects of myth belongs to Jena romantic school,while members of Heidelberg group examined myth by means of specific scientific methods, primarilycomparative-historical. In general, this article uncovers, that the merit of the German Romantics to the science ofmythology is difficult to overestimate.Keywords: German Romanticism, culture, myth, mythology, symbol.